2016
DOI: 10.1007/s00220-016-2753-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Asymptotic Stability of the Lane-Emden Solutions for the Viscous Gaseous Star Problem with Degenerate Density Dependent Viscosities

Abstract: The nonlinear asymptotic stability of Lane-Emden solutions is proved in this paper for spherically symmetric motions of viscous gaseous stars with the density dependent shear and bulk viscosities which vanish at the vacuum, when the adiabatic exponent γ lies in the stability regime (4/3, 2), by establishing the global-in-time regularity uniformly up to the vacuum boundary for the vacuum free boundary problem of the compressible Navier-Stokes-Poisson systems with spherical symmetry, which ensures the global exi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 44 publications
1
54
0
Order By: Relevance
“…Moreover, if considering the non-isentropic Euler equations (µ = λ = κ = 0) of ρ, u and S, then the sound speed is given by ∂p(ρ,S) ∂ρ = γ p ρ = √ γRθ. Therefore, the singular condition on the derivatives of the temperature profiles (2.9) coincides with the physical vacuum condition for the isentropic fluids ( [24,8,39]) in certain sense.…”
Section: The Reference Domainmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, if considering the non-isentropic Euler equations (µ = λ = κ = 0) of ρ, u and S, then the sound speed is given by ∂p(ρ,S) ∂ρ = γ p ρ = √ γRθ. Therefore, the singular condition on the derivatives of the temperature profiles (2.9) coincides with the physical vacuum condition for the isentropic fluids ( [24,8,39]) in certain sense.…”
Section: The Reference Domainmentioning
confidence: 72%
“…As it is pointed out by Liu in [33], such a singularity of the density makes the standard hyperbolic method fail in establishing the local wellposedness theory for the inviscid flow. Only recently, the local well-posedness theory for inviscid flows is developed by Coutand, Lindblad and Shkoller [7,8,9], Jang and Masmoudi [24,25], Gu and Lei [13,14], Luo, Xin and Zeng [39] in variant settings. See [22,10] for the viscous case.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize that the physical vacuum profiles mentioned here commonly exist in a lot of physical models, such as, the gaseous star problem, the Euler damping equations, etc. We refer these results to [29,30,31,50].However, the studies of free boundary problems mentioned above mainly concern the isentropic flows. We start the study of free boundary problem for non-isentropic flows by studying the equilibria of the radiation gaseous stars in [22], in which we establish the corresponding degeneracy of density and temperature near the vacuum boundary.…”
mentioning
confidence: 99%
“…Due to the balance between flow pressure and gravity force, it was shown that there is a critical value γ c = 4 3 in spatial three-dimension, the stationary Lane-Emden solution is expected to be stable for γ > 4 3 and instable for γ < 4 3 . Indeed, Jang and Tice [9] prove the instability theory of the NSP equations for 6 5 < γ < 4 3 , and the nonlinear asymptotic stability of the Lane-Emden solutions for the viscous gaseous star is established by Luo-Xin-Zeng [14,15] for 4 3 < γ < 2. For γ = 6 5 , the nonlinear instability is proved for gravitational Euler-Poisson system in [7].…”
Section: Introduction and Main Resultsmentioning
confidence: 94%
“…On the other hand, for 1 < γ < 6 5 , there are no stationary solutions with finite total mass. Recently, many important study on the asymptotic stability/instability of stationary solutions has been made, for instance, in [2,12,9,7,14,15,16]. Due to the balance between flow pressure and gravity force, it was shown that there is a critical value γ c = 4 3 in spatial three-dimension, the stationary Lane-Emden solution is expected to be stable for γ > 4 3 and instable for γ < 4 3 .…”
Section: Introduction and Main Resultsmentioning
confidence: 99%